Equivalent Circuit Analysis of Photovoltaic-Thermoelectric Hybrid Device with Different TE Module Structure. (7th May 2014) - Chen, Haijun; Wang, Ning; He, Hongcai
Abstract : Combining two different types of solar cells with different absorption bands into a hybrid cell is a very useful method to improve the utilization efficiency of solar energy. The experimental data of dye-sensitized solar cells (DSSCs) and thermoelectric generators (TEG) was simulated by equivalent circuit method, and some parameters of DSSCs were obtained. Then, the equivalent circuit model with the obtained parameters was used to optimize the structure design of photovoltaic- (PV-) thermoelectric (TE) hybrid devices. The output power ( P o u t ) first increases to a maximum and then decreases by increasing the TE prism size, and a smaller spacing between p-type prism and n-type prism of a TE p-n junction causes a higher output power of TEG and hybrid device. When the spacing between TE prisms is 15 μ m and the optimal base side length of TE prism is 40 μ m, the maximum theoretical efficiency reaches 24.6% according to the equivalent circuit analysis. This work would give some enlightenment for the development of high-performance PV-TE hybrid devices.